Semantic Web - Wu, Gang (IntechOpen, 2010)
Having lived with the World Wide Web for twenty years, surfing the Web becomes a way of our life that cannot be separated. From latest news, photo sharing, social activities, to research collaborations and even commercial activities and government affairs, almost all kinds of information are available and processible via the Web. While people are appreciating the great invention, the father of the Web, Sir Tim Berners-Lee, has started the plan for the next generation of the Web, the Semantic Web. Unlike the Web that was originally designed for reading, the Semantic Web aims at a more intelligent Web severing machines as well as people. The idea behind it is simple: machines can automatically process or "understand" the information, if explicit meanings are given to it. In this way, it facilitates sharing and reuse of data across applications, enterprises, and communities. According to the organisation of the book, the intended readers may come from two groups, i.e. those whose interests include Semantic Web and want to catch on the state-of-the-art research progress in this field; and those who urgently need or just intend to seek help from the Semantic Web. In this sense, readers are not limited to the computer science. Everyone is welcome to find their possible intersection of the Semantic Web.